Creeping Minimalism and Subject Matter. Issue 6 (9th August 2020) - Simpson, Matthew
Abstract: The problem of creeping minimalism concerns how to tell the difference between metaethical expressivism and its rivals given contemporary expressivists' acceptance of minimalism about truth and related concepts. Explanationism finds the difference in what expressivists use to explain why ethical language and thought has the content it does. I argue that two recent versions of explanationism are unsatisfactory and offer a third version, subject matter explanationism. This view, I argue, captures the advantages of previous views without their disadvantages and gives us a principled and general characterisation of non-representational views about all kinds of language and thought.